COMPLEMENTARY FEEDING APPROACHES: CHARACTERISTICS, DIFFERENCES AND IMPACT ON CHILD DEVELOPMENT - Campos de Oliveira, Ana Thais; de Sousa Silva, Fernanda Tayla; Barreto Amaral, Sheyla Maria; Sousa da Silva, Felipe; Yngrydh Valente Silva, Ysabele; Silva Moura Miranda, Everlândia; Rocha Santos, Joene Vitória; Evaristo Miranda, Kelvi Wilson (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2021)
The term complementary feeding refers to including the first solid foods in the child’s diet after six months of age. The food introduction involves the Traditional, Responsive, Baby Led Weaning (BLW), Baby Led Introduction to Solids (BLISS) and Participatory approaches. This work aimed to identify the main characteristics and differences of complementary feeding approaches in the scientific literature, and to present an infographic of food assembly and its different textures. This study is a narrative literature review, developed from searching for articles in the PubMed, CAPES journals and Google Academic electronic databases. Scientific materials were selected after reading the titles and abstracts, specifying the researchers’ references and briefly checking the texts. After analysis, it was possible to distinguish the main characteristics about each complementary feeding approach, and identify the low scientific volume for BLW and BLISS regarding the benefits and distinctions between the approaches.